2022
DOI: 10.3390/foods11172566
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preferments on the Physicochemical and Sensory Quality of Traditional Panettone

Abstract: In Peru, panettones are consumed in July and December. The main ingredient of panettones is wheat flour, which can be replaced with substitute flours to improve their nutritional, textural and sensory properties. This study aimed to evaluate the physicochemical, textural and sensory characteristics of panettones produced with three preferments, namely, biga (PB), sourdough (PMM) and sponge (PE), with the substitution of red quinoa flour and amaranth compared with a commercial product (PC). A completely randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
(48 reference statements)
3
5
0
Order By: Relevance
“…sabellica) in powder [ 22 ] and the addition of mesquite flour (Prosopis juliflora) with a lower volume and porosity [ 23 ]. The apparent density and specific volume did not show significant differences ( p ≥ 0.05) between the treatments; this behavior was reported by Jamanca et al [ 24 ] in pre-fermented panettone with quinoa and kiwicha.…”
Section: Resultssupporting
confidence: 80%
“…sabellica) in powder [ 22 ] and the addition of mesquite flour (Prosopis juliflora) with a lower volume and porosity [ 23 ]. The apparent density and specific volume did not show significant differences ( p ≥ 0.05) between the treatments; this behavior was reported by Jamanca et al [ 24 ] in pre-fermented panettone with quinoa and kiwicha.…”
Section: Resultssupporting
confidence: 80%
“…From these equations, the behavior can be obtained when increasing or reducing the flours studied so that it can be analyzed which variables to prioritize in a food product. Various studies have shown that the combination of wheat, quinoa and kiwicha flours can improve properties such as yeast performance, mechanical properties of the dough, water absorption in the dough, shelf life, structure and texture of the baked product [ 50 , 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Color registration was carried out using the CIE-L* a* b* system. In this system, L* represents the luminosity, a* indicates the hue on the green (−)-to-red (+) axis and b* indicates the hue on the blue (−)-to-yellow (+) axis [30] and CIE-L*c*h*, where L denotes luminosity, c denotes chroma or saturation and h denotes the hue or hue angle [37].…”
Section: Crumb and Crust Color Testmentioning
confidence: 99%
“…Elasticity and cohesiveness were similar among most samples (p > 0.05), except for T3 and T4, respectively. The elasticity of panettone dough is influenced by the amount of gluten present in the flour, as well as the addition of ingredients such as eggs, milk, or fats [30]. Prolonged kneading or longer fermentation time can cause the development of a stronger gluten network, resulting in a more elastic dough [45].…”
Section: Instrumental Texture Analysismentioning
confidence: 99%
See 1 more Smart Citation